2006
DOI: 10.1038/oby.2006.153
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Adipose Tissue‐Derived Monocyte Chemoattractant Protein‐1 Plays a Crucial Role in Adipose Tissue Macrophage Migration and Activation in Obese Mice

Abstract: YU, RINA, CHU-SOOK KIM, BYUNG-SE KWON, AND TERUO KAWADA. Mesenteric adipose tissue-derived monocyte chemoattractant protein-1 plays a crucial role in adipose tissue macrophage migration and activation in obese mice. Obesity. 2006;14:1353-1362. Objective: To determine whether chemokines, which play a pivotal role in monocyte/macrophage trafficking, modulate macrophage infiltration into and activation in the adipose tissues. Research Methods and Procedures: Various types of adipose tissue were isolated from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 19 publications
4
134
1
3
Order By: Relevance
“…Yu et al demonstrated that MCP-1 was upregulated at the mRNA and protein levels in the mesenteric, epididymal, subcutaneous and perirenal white AT of DIO mice, with the highest upregulation being in the mesenteric fat [59]. They likewise observed increased gene expression of the macrophage markers F4/80 and CD68 in AT beds [59].…”
Section: Chemokinesmentioning
confidence: 86%
See 3 more Smart Citations
“…Yu et al demonstrated that MCP-1 was upregulated at the mRNA and protein levels in the mesenteric, epididymal, subcutaneous and perirenal white AT of DIO mice, with the highest upregulation being in the mesenteric fat [59]. They likewise observed increased gene expression of the macrophage markers F4/80 and CD68 in AT beds [59].…”
Section: Chemokinesmentioning
confidence: 86%
“…They likewise observed increased gene expression of the macrophage markers F4/80 and CD68 in AT beds [59]. In addition, they performed in vitro migration experiments showing increased macrophage migration to mesenteric AT-conditioned media, which was blocked in response to an antibody for MCP-1 [59].…”
Section: Chemokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…5). In general, intra-abdominal AT of rodents and humans is more susceptible to M⌽ infiltration, is a greater source of inflammatory mediators, and may contribute more to some metabolic complications of obesity than subcutaneous AT (25,26,(41)(42)(43)(44). Removal of intra-abdominal AT in rodents ameliorates DIO-associated insulin resistance (26) and prevents insulin resistance and glucose intolerance of aging (25).…”
Section: Discussionmentioning
confidence: 99%